Murine typhus: a forgotten infection - Godinho, F.; Soares, M.; Soares, I.; Abecasis, P. (Portuguese Journal Internal Medicine, 2002)
The authors present a typical case of mild murine typhus, in which the usual epidemiologic and clinical aspects were present, but the diagnosis was only made retrospectively and was not considered when the patient first presented. The causes of the late diagnosis and its implications for patient care, which lead to unnecessary investigation and significant morbidity and mortality due to treatment-delay, are discussed.